A digital method for calculation the forming cutter profile in machining helical surface. (May 2019) - He, Kun; Li, Guolong; Du, Yanbin; Tang, Ying
Highlights: A point-vector envelope (PVE) digital method is proposed to calculate the forming cutter profile. The defined point-vector (PV) contains the discrete point and the corresponding normal vector. The PVE approximation algorithm is constructed to determine the envelope points of PV groups. The method can reflect the instant contact line and realize complete simulation of the enveloping process. Abstract: In the forming process of helical surface, the forming cutter profile has a decisive influence on machining accuracy. In this paper, a point-vector envelope (PVE) method is proposed to calculate the forming cutter profile of a helical surface. Firstly, the transverse profile of the helical surface is dispersed into a series of points based on the principle of average, and add corresponding normal vector to the discrete point for obtaining the point-vector (PV), and use the helical motion of PVs to envelope the forming cutter profile. Then, through the coordinate transformation and projection of PVs, the PV groups are formed on the calculation plane. A PVE approximation algorithm is constructed to determine all the envelope points of the PV groups, and the grinding wheel profile is obtained by fitting all the envelope points into curves. Finally, the validity of the proposed digital method is demonstrated in numerical and experimental example of the helical gear form grinding. Graphical abstract: Image, graphical abstract